Monastic reform as process : realities and representations in medieval Flanders, 900-1100 - Vanderputten, Steven (Ithaca : Cornell University Press, 2013)
Careful study of reforms in the early tenth century at seven Benedictine monastaries of the Lotharingian "mixed observance" at: Saint Bertin, Bergues-Saint-Winnoc, Marchiennes, Saint-Amand, Saint-Bavo, Saint-Peter, and Saint-Vaast. Strives to demonstrate a more nuanced view of monastic reforms of this time period.
Corporate memories of reform -- The "failed" reforms of the tenth century -- The "dark age" of Flemish monasticism -- Introducing the new monasticism -- Processes of reformist government -- Shaping reformed identities -- The "waning" of reformed monasticism.
Includes bibliographical references and index.
Print version record.
In English.
Master record variable field(s) change: 650, 651
Keywords: Monasticism and religious orders -- France -- Flanders -- History -- Middle Ages, 600-1500.; Monasticism and religious orders -- Belgium -- Flanders -- History -- Middle Ages, 600-1500.; Flanders (France) -- Church history; Flanders (Belgium) -- Church history; HISTORY -- Medieval; RELIGION -- Institutions & Organizations; Monasticism and religious orders -- Middle Ages; Belgium -- Flanders; France -- Flanders; Klosterreform; Ordensleben; Flandern; 600-1500; Electronic books; Church history; History